Digital Information Security: Coronavirus Crisis Impact on the Accountants, Business Analysts and Auditors Training - Nazarova, Karina; Nezhyva, Mariia; Metil, Tetіana; Hordopolov, Volodymyr; Prystupa, Liudmyla; Moyseyenko, Olesya (Problemy Ekorozwoju, 2022)
The article considers the impact of transformation processes on business in the context of digitalization. Equally important is the study of the impact of these processes on the training of professionals whose work has had a direct impact on these transformations – accountants, business analysts and auditors. These specialists are faced with the task of analyzing the impact of the facts and determining the change in business development strategy in the context of global digitalization. The field of audit both in the world was able to adapt extremely flexibly to the new realities of functioning in the digitalized world. In this article, the authors reveal the main trends of digitalization of audit in the conditions of economic transformation and limited business practices caused by this global pandemic of 2019-2020. At the same time, the processes of digital transformation are the driving forces of the economy. Computer technology is becoming increasingly involved in reforming the audit institution and changing the trajectory of the auditor’s role in such a society.